Usefulness of Chlamydia serology in prediction of tubal factor infertility among infertile patients at Federal Medical Centre, Bida, North Central Nigeria - Amadi, Lucky; Onwudiegwu, Uchenna; Adeyemi, Adebanjo B.; Nwachukwu, Chiemezie N. D.; Abiodun, Afolabi B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is a major public health problem in developing countries where pelvic inflammatory disease due mainly to Chlamydia trachomatis and Neisseria gonorrhea infection have been implicated. The role of Chlamydia serology in predicting tubal factor infertility (TFI) has been demonstrated by many researchers elsewhere. However, there are limited data in our environment. This prospective cross-sectional study aims to determine the usefulness of Chlamydia Serology as a screening tool for TFI at Federal Medical Centre, Bida, North Central Nigeria. Methods: 125 women with infertility who met the inclusion criteria were enrolled into the study. Relevant information on their socio-demographic characteristics, gynaecological symptoms and risks factors for infertility were obtained. Participants had Hysterosalpingography (HSG) as part of their fertility work-up while 5ml of venous blood was withdrawn to check for Immunoglobulin G antibody to Chlamydia trachomatis using rapid test kits. The HSG findings were correlated with the result of Chlamydia serology. Data was analyzed using the computer software, Statistical Package for Social Science (SPSS) version 20. The level of significance (p value) was set at 0.05. Results: A total of 120 infertile women completed the study, 5 had incomplete investigations and were excluded from the analysis. The prevalence of TFI was 47.5%, while that of positive chlamydia serology was 36.5%. The prevalence of chlamydial seropositivity was 59.6% for patients with TFI but 15.9% for non-TFI. There was a significant association between positive chlamydia serology and TFI p< 0.05. The study revealed moderate sensitivity 59.6%, and negative predictive value 69.7% but high specificity 84.1% and positive predictive value of 77.2%. In this study the odds for diagnosing tubal infertility was 7.8. Conclusions: Chlamydia serology is useful in predicting TFI and should be incorporated in the routine work up for infertility.